2017
DOI: 10.12944/cwe.12.3.20
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation Potential of Sesuvium Portulacastrum on Remediating Salt Affected Soil

Abstract: Sesuvium portulacastrum is a salt hyper accumulating plant and pioneer plant species used for desalination and phytoremediation. The plant tolerates abiotic constraints such as salinity and drought. It grows under severe salinity and it can be used for the remediation and restoration of salt contaminated soils affected from industrial effluents. Among the major water demanding industries, the textile industry has biggest impact on the environment related to primary water consumption and waste water discharge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…An EC of 4 dS/m is equivalent to 40 mM of NaCl ( Marschner, 2011 ). Studies have shown that S. portulacastrum can grow in soils with 100 mM NaCl ( Slama et al., 2008 ) and has an EC of 13.04 dS/m ( Ramaswamy et al., 2017 ); thus, S. Portulacastrum can grow in different saline soils.…”
Section: Sea Purslane Production and Utilizationmentioning
confidence: 99%
“…An EC of 4 dS/m is equivalent to 40 mM of NaCl ( Marschner, 2011 ). Studies have shown that S. portulacastrum can grow in soils with 100 mM NaCl ( Slama et al., 2008 ) and has an EC of 13.04 dS/m ( Ramaswamy et al., 2017 ); thus, S. Portulacastrum can grow in different saline soils.…”
Section: Sea Purslane Production and Utilizationmentioning
confidence: 99%